Perangkat Lunak Sistem Penerimaan Peserta Didik Baru Menggunakan Framework Codeigniter pada MTs Miftahul Huda Tegal Sari - Muslikhun, Imam; Nasir, Muhammad; Fatoni (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The New Student Admission Program (PPDB) is an annual program at MTS Miftahul Huda Tegal Sari. Previously, the new student admission process was done manually, requiring physical visits to the school to fill out registration forms and gather information. This was not effective. Therefore, this research has created an online system for new student admissions. Using the waterfall method, data was collected through observations, interviews, and literature studies. The result is a web-based PPDB information system using the CodeIgniter framework, which simplifies the admission process for prospective students and schools. This system is expected to assist the PPDB committee in managing new student data more effectively and efficiently. Information technology-based PPDB has great potential to enhance the management of the student admission process in schools.